ISSUES IN THE MULTILINGUAL INFORMATION PROCESSING OF SPOKEN POLITICAL AND JOURNALISTIC TEXTS. - Alexandris, Christina (Cambridge Scholars Publishing, 2020)
From television screens to mobile phones, spoken political and journalistic texts in the media are accessible to recipients of almost any kind, including the international public. These texts constitute a remarkable source of empirical data for human behaviour and for linguistic phenomena, but pose significant challenges in terms of their evaluation, processing and translation due to a set of distinctive characteristics. This volume presents and describes a number of features of spoken political and journalistic texts, and proposes strategies for their correct and efficient analysis and proces.